Trends and Utilization of Ankle Arthroplasty vs Arthrodesis in the State of New York, 2009-2018. Issue 4 (November 2022) - Brodeur, Peter G.; Modest, Jacob M.; Walsh, Devin F.; Hartnett, Davis A.; Gil, Joseph A.; Cruz, Aristides; Hsu, Raymond Y.
Category: Ankle Arthritis; Ankle Introduction/Purpose: The two most common surgical procedures for end stage ankle arthritis patients who fail conservative management are arthrodesis and arthroplasty. The appropriateness of total ankle arthroplasty versus arthrodesis remains controversial. The long-term outcomes of current generation prostheses are not yet available and there is continued debate regarding the cost-benefit and risk-benefit analysis of each procedure. This study seeks to document rates of arthroplasty and arthrodesis for ankle osteoarthritis in New York in order to ascertain utilization of each procedure over time and stratification by patient demographics. Methods: Patients from 2009-2018 were identified using International Classification of Disease (ICD)-9 and 10 Clinical Modification (CM) codes for ankle osteoarthritis and Current Procedural Terminology or ICD-9 CM and ICD-10 Procedural Classification System procedural codes for ankle arthrodesis or ankle arthroplasty in the New York Statewide Planning and Research Cooperative System (SPARCS) database. SPARCS is an all-payer database collecting outpatient (emergency department, ambulatory surgery, and hospital-based clinic visits) and all inpatient claims in New York. A trend analysis was performed to determine if there was a shift towards either ankle arthrodesis or ankle arthroplasty over time. A multivariable logistic regression was performed to assess the impact of patient demographic factors on the likelihood of receiving arthrodesis versus arthroplasty. The variables included in the analysis were age, sex, race, ethnicity, Social Deprivation Index (linked by ZIP code), Charlson Comorbidity Index, and primary insurance type. Results: 3, 735 cases were included in the trend analysis in years 2009-2018. In 2009, 220 (84%) procedures were ankle arthrodesis and 42 (16%) were ankle arthroplasty. By 2018, 274 (43.2%) were ankle arthrodesis and 360 (56.8%) were ankle arthroplasty (p<.0001). Ankle arthrodesis increased 25% over the study period while ankle arthroplasty increased 757%. The multivariable logistic regression showed older age (OR: 0.95, p<.0001) and females (OR: 0.71, p=.0003) had decreased odds of arthrodesis. African American race (OR: 1.63, p=.0459), federal insurance (OR: 1.72, p<.0001), worker's compensation (OR: 1.75, p=.0072), being from an area with higher social deprivation (OR: 1.01, p=.0004) or having >=1 Charlson comorbidities (OR: 1.4, p=.0007) was associated with increased odds of arthrodesis compared to arthroplasty. Conclusion: The present study demonstrates a substantial rise in ankle arthroplasty volume without a matching decrease in ankle arthrodesis volume over ten years. Patients who are wary of the motion limitation of arthrodesis and would previously have gravitated towards nonoperative management may now be finding a commonly performed, motion sparing alternative in arthroplasty. Ankle arthrodesis volume slightly increased, suggestive of nonequivalent patient populations undergoing these two procedures. There are apparent socioeconomic disparities in the utilization of these procedures, likely stemming from numerous nuanced factors but nevertheless also likely reflective of disparities in foot and ankle healthcare access.